Respuesta :

Answer:

[tex]3x^2 - 10x -5[/tex]

Step-by-step explanation:

[tex]g(f(x))=g(x-1) \\ \\ =3(x-1)^2-4(x-1)-12 \\ \\ =3(x^2-2x+1)-4(x-1)-12 \\ \\ =3x^2-6x+3-4x+4-12 \\ \\ =3x^2 - 10x -5[/tex]

Answer:

[tex]g(f(x))=3x^2-10x-5[/tex]

Step-by-step explanation:

Given functions:

[tex]\begin{cases}f(x)=x-1\\g(x)=3x^2-4x-12\end{cases}[/tex]

Function composition is an operation that takes two functions and produces a third function.

Therefore, the given composite function g(f(x)) means to substitute function f(x) in place of the x in function g(x):

[tex]\begin{aligned}\implies g(f(x))&=g(x-1)\\& = 3(x-1)^2-4(x-1)-12\\&=3(x-1)(x-1)-4x+4-12\\&=3(x^2-2x+1)-4x-8\\&=3x^2-6x+3-4x-8\\&=3x^2-6x-4x+3-8\\&=3x^2-10x-5\end{aligned}[/tex]

Learn more about composite functions here:

https://brainly.com/question/28010848